Nikolaevskoe city school in Tyumen. Research materials - A. I. Klimenko; V. V. Yugai (Архитектура, строительство, транспорт)
The article is devoted to the study of the building of former Nikolaevskoe city school in Tyumen. The Institute of Design, Reconstruction and Restoration of Urban Environment Objects of LLC "Tyumenproekt" under the direction of Alexander I. Klimenko carried out a comprehensive scientific study, including historical and archival and bibliographic sources, as well as materials of field research, and made the most reliable graphic reconstruction of the object. The materials of the study may become the basis for further work, including the restoration project of building and its adaptation to the modern conditions of city life.